KNOWLEDGE AND ANTENATAL CARE VISITS AS PREDICTORS OF THE DECISION TO GIVE BIRTH AT HOME - Sunesni Sunesni; Mekar Zenni Radhia; Dian Furwasyih (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Home birth selection is a complex decision influenced by various factors. This study aimed to determine the relationship between knowledge and antenatal care (ANC) visits with the decision-making of home birth in the working area of Mapaddegat Public Health Center, Mentawai Islands Regency. This research was a descriptive analytic study with a case-control design, conducted from February to May 2025, involving mothers who gave birth and were recorded in the maternal cohort data from January 2023 to December 2024. A systematic random sampling technique was applied, consisting of 21 respondents in the case group and 42 respondents in the control group. Data were analyzed using univariate and bivariate analysis with the chi-square statistical test. The univariate results showed that 74.6% had high knowledge, and 57.2% had more than four ANC visits. The bivariate analysis revealed a significant relationship between knowledge (p = 0.011; OR = 5.455) and the number of ANC visits (p = 0.015; OR = 4.462) with the decision to give birth at home. It can be concluded that there is a relationship between knowledge and the number of ANC visits with home birth decision-making. It is recommended for the Mapaddegat Public Health Center staff to strengthen health promotion regarding delivery in health facilities and develop innovations to increase the coverage of facility-based deliveries.